1995
DOI: 10.1007/bf01519627
|View full text |Cite
|
Sign up to set email alerts
|

Immune parameters of mice bearing human head and neck cancer

Abstract: A xenogeneic human head and neck squamous cell carcinoma (HNSCC) model in immunocompetent mice was evaluated for its requirement of cyclosporine for progressive tumor growth. Tumor growth and T cell functions were assessed in mice receiving cyclosporine treatment for various lengths of time. Tumor cells were injected s.c. on day 1 and cyclosporine was injected i.p. daily on days 1, 1-7, 1-14, 1-21, or for the entire 28 days of tumor growth. All mice developed tumors. These tumors were confirmed to be squamous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…One potentially exciting new area for tumor surveillance in HNSCC is in the area of immunological markers. The immune suppressive effects of HNSCC are well known and are due to the production of immunosuppressive cytokines and the induction of a population of CD34+ natural suppressor cells [106]. We have demonstrated that high intratumoral CD34+ content and synthesis of high levels of granulocyte-macrophage colony-stimulating factor correlate significantly with local recurrence and distant metastasis [107].…”
Section: Biological Predictors Of Metastasismentioning
confidence: 71%
“…One potentially exciting new area for tumor surveillance in HNSCC is in the area of immunological markers. The immune suppressive effects of HNSCC are well known and are due to the production of immunosuppressive cytokines and the induction of a population of CD34+ natural suppressor cells [106]. We have demonstrated that high intratumoral CD34+ content and synthesis of high levels of granulocyte-macrophage colony-stimulating factor correlate significantly with local recurrence and distant metastasis [107].…”
Section: Biological Predictors Of Metastasismentioning
confidence: 71%
“…(3). Such an immune escape mechanism has also been suggested for HNSCC cells and might be reflected by a low T cell infiltration of tumors or by inefficient activation and generation of HNSCC-associated antigenspecific CTL as described by several investigators (20,22,25). Restoration of antigen presentation by cytokine treatment and/or gene transfer of deficient APM component consequently renders cells sensitive to CTL-mediated lysis.…”
Section: Discussionmentioning
confidence: 91%
“…Samples may be further dispersed enzymatically using trypsin, DNase, collagenase or a combination thereof [ 19 ]. The cell suspension was then placed into a rich culture medium, such as DMEM or RPMI-1640 with additional fetal bovine serum (FBS) and transferred to petri-dishes or culture flasks [ 20 , 21 , 22 ]. A combination of antibiotics and antimycotics was added to prevent bacterial or fungal overgrowth, and fibroblast overgrowth was managed through selective trypsinisation or cell scraping [ 12 ].…”
Section: Resultsmentioning
confidence: 99%